Human attention in digital environments - Roda, Claudia (Cambridge University Press, 2011)
"Digital systems, such as phones, computers and PDAs, place continuous demands on our cognitive and perceptual systems. They offer information and interaction opportunities well above our processing abilities, and often interrupt our activity. Appropriate allocation of attention is one of the key factors determining the success of creative activities, learning, collaboration, and many other human pursuits. This book presents research related to human attention in digital environments. Original contributions by leading researchers cover the conceptual framework of research aimed at modelling and supporting human attentional processes, the theoretical and software tools currently available, and various application areas. The authors explore the idea that attention has a key role to play in the design of future technology and discuss how such technology may continue supporting human activity in environments where multiple devices compete for people's limited cognitive resources"--